Survey of instructions for authors on how to report an update of a systematic review: guidance is needed. Issue 2 (30th January 2017) - Pieper, Dawid; Mathes, Tim
Abstract : Systematic reviews have become the cornerstone of evidence-based healthcare. Approximately half of the systematic reviews are out of date after 5.5 years, and keeping them up to date remains a huge challenge. Despite new guidance on when and how to update systematic reviews, there seems to be a lack of guidance on how to report updates of systematic reviews. Therefore, we decided to systematically analyse instruction for authors in biomedical journals regarding guidance on reporting updates of systematic reviews. We conducted a survey investigating 250 journals. The journal list was derived by a twofold strategy. First, we chose a list of journals that were included in a recently published survey of systematic reviews. This list was augmented by a PubMed search for published updates of systematic reviews. For each journal, we checked the instructions for authors for any content or links related to updating systematic reviews in September 2016. Out of 250 journals, we found only one with guidance clearly related to updates of systematic reviews, namely the BioMed Central journal, Systematic Reviews . Nevertheless, concrete guidance on reporting is lacking as it is stated that authors are encouraged to be innovative in how to report and present systematic review updates. This makes clear that there remains a fundamental uncertainty of how authors willing to update a previously published systematic review should act as even the leading journal in evidence syntheses does not have clear guidance. Debate is necessary on how to report updates of systematic reviews.